Modulation of single motor unit discharges using magnetic stimulation of the motor cortex in incomplete spinal cord injury. Issue 4 (1st April 2000) - Smith, H C; Davey, N J; Savic, G; Maskill, D W; Ellaway, P H; Jamous, M A; Frankel, H L
Abstract : OBJECTIVES: Motor evoked potentials (MEPs) and inhibition of voluntary contraction to transcranial magnetic stimulation (TMS) of the motor cortex have longer latencies than normal in patients with incomplete spinal cord injury (iSCI) when assessed using surface EMG. This study now examines the modulation of single motor unit discharges to TMS with the aim of improving resolution of the excitatory and inhibitory responses seen previously in surface EMG recordings. METHODS: A group of five patients with iSCI (motor level C4-C7) was compared with a group of five healthy control subjects. Single motor unit discharges were recorded with concentric needle electrodes from the first dorsal interosseus muscle during weak voluntary contraction (2%–5% maximum). TMS was applied with a 9 cm circular stimulating coil centred over the vertex. Modulation of single motor unit discharges was assessed using peristimulus time histograms (PSTHs). RESULTS: Mean (SEM) threshold (expressed as percentage of maximum stimulator output (%MSO)) for the excitatory peak (excitation) or inhibitory trough (inhibition) in the PSTHs was higher (p<0.05) in the patients (excitation=47.1 (5.9) %MSO; inhibition=44.3 (3.2) %MSO) than in controls (excitation=31.6 (1.2) %MSO; inhibition=27.4 (1.0) %MSO). Mean latencies of excitation and inhibition were longer (p<0.05) in the patients (excitation=35 (1.8) ms; inhibition=47.1 (1.8) ms) than in the controls (excitation=21.1 (1.6) ms; inhibition=27 (0.4) ms). Furthermore, the latency difference (inhibition−excitation) was longer (p<0.05) in the patients (10.4 (2.1) ms) than in the controls (6.2 (0.6) ms). CONCLUSION: Increased thresholds and latencies of excitation and inhibition may reflect degraded corticospinal transmission in the spinal cord. However, the relatively greater increase in the latency of inhibition compared with excitation in the patients with iSCI may reflect a weak or absent early component of cortical inhibition. Such a change in cortical inhibition may relate to the restoration of useful motor function after iSCI.